‘Stop’ that ambulance! New physics at the LHC? - Kim, Jong Soo; Tattersall, Jamie (Journal of high energy physics, 2014)
A number of LHC searches now display intriguing excesses. Most prominently, the measurement of the W+W− cross-section has been consistently ∼ 20% higher than the theoretical prediction across both ATLAS and CMS for both 7 and 8 TeV runs. More recently, supersymmetric searches for final states containing two or three leptons have also seen more events than predicted in certain signal regions. We show that a supersymmetric model containing a light stop, winos and binos can consistently match the data. We perform a fit to all measurements and searches that may be sensitive to our model and find a reduction in the log-likelihood of 15.4 compared to the Standard Model which corresponds to 3.5-σ once the extra degrees of freedom in the fit are considered.
Gesehen am 22.10.2020